The Likelihood of Confusion in the United State Ninth Circuit and the doctrine of Confusable Marks in the Andean Tribunal - Cabrera Perdomo, Francisco José (Revista Tribuna Internacional, 2016)
The article analysis the most important cases within the jurisdiction of California regarding the trademark infringement and its prerogative of the likelihood of confusion. Finally, it compares the conclusion with the confusable marks theory within the Andean community’s recent cases solving the issue.